Has globalisation really had no effect on unions? - Axel Dreher; Noel Gaston (ETH Zurich, KOF Swiss Economic Institute, 2005)
For a number of OECD countries, the deterioration of labour market outcomes for less-skilled workers since the early 1980's has coincided with a steady decline in union membership. Globalisation is commonly believed to have contributed to both developments. However, recent studies fail to find support for the presumption that globalisation adversely affects unions. Revisiting this issue by using a novel globalisation index we find that globalisation has indeed contributed to deunionisation. In delving further into the issue, we find that it is social integration, rather than economic or political integration, that has been the main contributor to the decline in union membership.
Keywords: F02; J50; O57; C82; 330; Deunionisation; globalisation; integration; panel regressions; Globalisierung; Gewerkschaftsbewegung; Gewerkschaftsmitgliedschaft; Panel